TREATMENT OUTCOMES OF LUMBAR SPINAL STENOSIS WITH INSTABILITY IN OSTEOPOROTIC PATIENTS AT THONG NHAT HOSPITAL - Bá Tùng, Lê; Trung Kiên, Trần (Journal of Health and Aging, 2025)
To evaluate the treatment outcomes of lumbar spinal stenosis with instability in osteoporotic patients at Thong Nhat Hospital. A retrospective descriptive case series study on all cases of lumbar spinal stenosis with instability accompanied by osteoporosis (T-score < -2.5 SD) who underwent posterior lumbar interbody fusion (PLIF) combined with pedicle screw fixation using cement augmented cannulated screws at the Neurosurgery Department of Thong Nhat Hospital, Ho Chi Minh City, from June 2015 to June 2021. Among 59 patients meeting the inclusion criteria, all showed postoperative recovery. Nearly 50% had excellent outcomes, with significant reductions in back pain and a mean motor recovery time of 23 days post-surgery. According to the Japanese Orthopaedic Association (JOA) score: 49.1% had excellent improvement, 39% good, 11.9% moderate, and no poor outcomes were observed. Preoperative vs. discharge clinical symptoms showed significant improvement: VAS score for back pain decreased from 7.1 to 3.4 (p < 0.05), radicular leg pain from 6.44 to 3.76 (p < 0.05), and neurogenic claudication reduced from 68.12% to 7.2% (p < 0.05). According to Lee’s fusion assessment criteria: 72.9% achieved definite fusion (Grade A), 25.4% probable fusion (Grade B), and only one case showed pseudoarthrosis. Complications were rare and included cement leakage, surgical site infection, and dural tear. JOA score improvements were more pronounced in patients with 1 or 2 fusion levels and significantly higher in those with 3-level fusions. Posterior lumbar interbody fusion using cement-augmented cannulated screws is an effective surgical treatment for lumbar spinal stenosis with instability in osteoporotic patients, offering good recovery outcomes.